Efektivitas Multimedia Interaktif Berbasis Smartphone untuk Pembelajaran Matematika dengan Tatap Muka Terbatas - Muhamad Ansar Muzakkir; Sarson W. Dj. Pomalato; Muhammad Rifai Katili (Department of Mathematics, Universitas Negeri Gorontalo, 2022)
This research is a type of research and development that aims to develop and test the effectiveness of using smartphone-based interactive multimedia products using smart apps creator (SAC), which was developed through the development of the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The research subjects were teachers and students of class X IPA 1 SMAN 4 Gorontalo, as many as 28 students. The product is considered suitable for use based on the validity criteria from the assessment of the material, media, and learning design experts. The product is also considered effective based on the learning outcomes of students with a one-group pretest-posttest experimental design. From the results of statistical analysis with the paired sample T-test where the value of is 12,560 and the value of is 2,05183, then . So, the hypothesis that there are differences in learning outcomes before using the product and after using the multimedia product is accepted. Then the effectiveness category is determined through the gain score test with the average gain score of 0.62 with a moderate classification and for the average percentage gain score of 62.25% with a fairly effective category.